HALAL INDUSTRY INFLUENCE ON STATE GDP - OIC COUNTRIES IN THE ASIAN REGION IN 2013 - 2016 - Ahmad Samsul Badi (Universitas Airlangga, 2019)
The purpose of this study is to Determine the relationship between the influence of Islamic finance, halal food and halal tourism to GDP in the OIC countries in 2013 - 2016. This is a quantitative study using data panel method. The Data used is secondary Data from Thomson Reuters in 2013 - 2016. The results Showed that Islamic finance, halal food and sharia tourism cumulatively to positively Affect show. From the results of the independent F-test in know that